The Effect of Different Anaesthetic Techniques on the Incidence of Thrombosis following Total Hip Replacement - Hoek, Jaap A; Henny, Ch Pieter; Knipscheer, Haye C; ten Cate, Hugo; Nurmohamed, Michael T; ten Cate, Jan W (Thrombosis and Haemostasis, 1991)
We performed a retrospective analysis on the influence of three types of anaesthesia on the incidence of deep vein thrombosis (DVT) following total hip replacement (THR) in consecutive patients randomized to either the low molecular weight heparinoid Otg 10172 (97 patients), of placebo (99 patients). Ninety patients were operated under epidural anaesthesia, 77 patients under psoas compartment block with additional inhalation anaesthesia, and 29 patients under general anaesthesia. DVT assessment was performed by bilateral venography between days 8 and 12 postoperatively. The overall incidence of DVT in the 196 patients was 37% in the epidural anaesthasia group, 35% in the psoas compartment block group, and 36% in the general anaesthesia group. Although the incidence of DVT in patients randomuedto placebo was similar in the two anaesthesia groups (53%), there was an important reduction of the occurrence of proximal DVT by the heparinoid in the psoas compartment block group (from 20 to 0%), compared to the epidural anaesthesia group (from 27 to l8%) (p <0.0061). Significant y more minor wound hematomas occurred in the psoas compartment block group as compared to the epidural anaesthesia group (p <0.05). Synergrsm of thrombin generation inhibition by the heparinoid and inhibition of plateletlggregation at the damaged vessel wall, by high local concentrations of bupivacaine in the psoas compartment block technique, is proposed as a possible mechanism behind this observation.